KOINONIA SEBAGAI MODEL PENGEMBANGAN PASTORAL PARIWISATA HOLISTIK DI KEUSKUPAN RUTENG - Manu, Maximus; Jewadut, Jean Loustar; Pasaribu, Astina Vebriani (Bahasa Indonesia, 2024)
The Ruteng Diocese Church expressed social concern for the pace of tourism development in Labuan Bajo by declaring 2022 as the year of holistic tourism. Holistic pastoral tourism seeks to integrate the economic, cultural, ecological, ethical, and spiritual dimensions of tourism. The scientific article aims to explore how coinonia can be used as a model in developing holistic pastoral tourism in the Diocese of Ruteng. The research used a method, is a qualitative analysis method with a literature study approach which includes analysis of documents, articles and books related to the theme being reviewed. Based on the research results, it was concluded that the coinonia aspect has a very important role in efforts to develop holistic pastoral tourism. The application of the coinonia model can increase collaboration between pastoral sectors such as families, schools, the younger generation, children and teenagers, as well as adherents of other religions. This collaboration can support sustainable tourism development. The author offers the coinonia model of the Ruteng Diocese Church which has sacramental values, solidarity, subsidiarity and liberation in every pastoral program as an effort to develop holistic tourism pastoralism.